Influence of a hot/wet environment on exercise performance in natives to tropical climate - Voltaire, B.; Berthouze-Aranda, S.; Hue, O. (The Journal of Sports Medicine and Physical Fitness, 2003)
Aim: The purpose of this study was to determine the influence of a hot/wet climate on thermoregulation and cardiac responses during a prolonged effort in natives to tropical climate. Methods: Experimental design: 22 healthy trained subjects volunteered to perform 3 trials of submaximal cycling of 1 hour each. Two of the trials were performed in a cool environment and the third, in tropical conditions. Measures: during all trials, we measured the evolution of tympanic temperature, water loss, heart rate performance. Results: The results showed 1) a significant increase in core temperature (p>0.001), heart rate (p<0.0001), sweat rate (p<0.0005) and water loss (p<0.0001) and 2) a significant impairent in performance, estimated at 27.7% (p<0.01), in tropical conditions as compared with a cool environment. Conclusion: We concluded that intensive and prolonged exercise in a hot/wet climate induces an overload regarding thermoregulatory and cardiac responses even in natives to tropical climate. The impaired physiological responses constitute a limiting factor for aerobic performance.